2008
DOI: 10.5694/j.1326-5377.2008.tb01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease and injury in Australia in the new millennium: measuring health loss from diseases, injuries and risk factors

Abstract: Objective: To describe the magnitude and distribution of health problems in Australia, in order to identify key opportunities for health gain. Design: Descriptive epidemiological models for a comprehensive set of diseases and injuries of public health importance in Australia were developed using a range of data sources, methods and assumptions. Health loss associated with each condition was derived using normative techniques and quantified for various subpopulations, risks to health, and points in time. The ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
383
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(395 citation statements)
references
References 8 publications
7
383
0
5
Order By: Relevance
“…Physical inactivity has been estimated to account for ~7% of the global health burden,5 accompanied by considerable economic costs for society 6. Based on this knowledge, international guidelines encourage people to engage in ≥30 min of at least moderate intensity PA daily 7.…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity has been estimated to account for ~7% of the global health burden,5 accompanied by considerable economic costs for society 6. Based on this knowledge, international guidelines encourage people to engage in ≥30 min of at least moderate intensity PA daily 7.…”
Section: Introductionmentioning
confidence: 99%
“…In previous versions of the GBD and the Australian Burden of Disease and Injury study, all hip fracture cases are given a disability weight of 0.372 (ie, a 37.2% decrement in health) for an initial period of 51 days for treated cases and 88 days for untreated cases 2 3. It is assumed that 5% of treated and 50% of untreated fractured femur cases have lifelong disability at a disability weight of 0.272.…”
Section: Introductionmentioning
confidence: 99%
“…Other health benefits include improvements in musculoskeletal function (strength, balance, flexibility), cardiorespiratory function (including blood pressure), glucose metabolism, body mass index, immune capacity, mental health and quality of life 30–33. Tai-chi could therefore affect key risk factors (physical inactivity, high body mass, high blood pressure) that explain considerable proportions of attributable health loss associated with cardiovascular disease, diabetes mellitus and, to a lesser extent, cancer 34. Anecdotal evidence suggested that most participants enjoyed tai-chi, generating direct ‘consumption’ benefits.…”
Section: Discussionmentioning
confidence: 99%